(untitled) (The Pakistan Development Review, 2000)
Population programmes in many developing countries have emphasised on family planning services driven largely by numbers and demographic targets. With the advent of the International Conference on Population and Development (ICPD) in 1994, it has been recognised to move beyond a narrow focus on family planning to a more comprehensive concern of reproductive health oriented towards meeting the needs of individuals and families. This advocated shift in population and development strategy, especially in health emphasises that services be offered to women, men and adolescents with a special focus on fulfilling women’s health needs, safeguarding their reproductive rights and involving men as equal partners in meeting the goal of responsible parenthood [United Nations (1995)]. In response to ICPD’s mandate, Pakistan’s population programme has increasingly been focussed on various aspects of reproductive health and is in the process of broadening the scope of services for a transition to reproductive health without losing focus on achieving fertility reduction goal. In this regard, the government has adopted a comprehensive population and development policy incorporating an array of reproductive health services and has integrated population and health departments and their activities in dealing with RH problems. Under the consideration that the revised programme can not simultaneously address all of the RH problems, an integrated National Reproductive Health Services Package has been developed to provide services to eligible women, men and adolescents [Pakistan (1999)]. The major components of RH package include: